PEMBENTUKAN DAN PENDAMPINGAN BANK SAMPAH MENGGUNAKAN SISTEM MANAJEMEN PENDUKUNG KEBERLANJUTAN DI MERUYA SELATAN, JAKARTA BARAT - Suzan Bernadetha Stephani; Harefan Arief; Niken Sulistyowati (Batara Wisnu : Indonesian Journal of Community Services, 2022)
The increase in the amount of waste is influenced by the consumption pattern of the people who always want everything practical and fast. On the other hand, the increase in the amount of waste has not been followed by changes in public awareness in its management. Heaps of waste that accumulate in the landfill and have not been managed properly will cause greenhouse gas emissions, one of which is methane (CH4). This gas is produced from solid waste and is more dangerous than CO2. Waste bank management is one of the logical and realistic solutions to be carried out in Indonesia, especially in urban areas such as Meruya Selatan Village, West Jakarta. Waste handling activities from upstream to downstream are mandated by Presidential Regulation number 97 of 2017 concerning National Policies and Strategies in Reducing and Handling Waste. Through good waste management, it is hoped that there will be a reduction in the amount of waste and greenhouse gas emissions that are targeted to be achieved by each City/Regency by 30% and waste management in a city system by 70% by 2025